Multifaceted Roles of Adipose Tissue-Derived Exosomes in Physiological and Pathological Conditions - Liu, Yunnan; Wang, Chen; Wei, Mengying; Yang, Guodong; Yuan, Lijun (Frontiers in Physiology, 2021)
Adipose tissue functions importantly in the bodily homeostasis and systemic metabolism, while obesity links to multiple disorders. Beyond the canonical hormones, growth factors and cytokines, exosomes have been identified to play important roles in transmission of information from adipose tissue to other organs. Exosomes are nanoscale membrane vesicles secreted by donor cells, and transfer the genetic information to the recipient cells where the encapsulated nucleic acids and proteins are released. In this review, we elaborate the recent advances in the biogenesis and profiling of adipose tissue derived exosomes, and their physiological and pathological effects on different organs. Moreover, the potential significance of the exosomes as therapeutic vehicles or drugs is also discussed.